Energy requirements for maintenance as a function of body weight and critical temperature in broiler chickens - Morillo, Freddy Alexander Horna [UNESP]; Macari, Marcos [UNESP]; Reis, Matheus de Paula [UNESP]; Teofilo, Guilherme Ferreira da Silva [UNESP]; Camargos, Rosiane de Souza [UNESP]; Sakomura, Nilva Kazue [UNESP] (Elsevier, 2023)
The rate of heat loss (HL) decreases as body weight (BW) increases, and this rate of HL is affected by environmental temperature (T); thus, a relashionship between BW and T on energy metabolism is expected. Therefore, this study was conducted to evaluate the relashionship between body weight (BW) and T on fasting heat production (FHP). A total of six respirometry chambers coupled with an indirect calorimetric system were used to measure the FHP of 76 groups of male broiler chickens (Cobb 500) subjected to different temperatures. The chamber temperatures were set to get temperatures below and above the Cobb 500 guideline recommendation for each age ranging from 15 to 36 °C. The average BW of these 76 groups of broiler chickens ranged from 0.20 to 3.30 kg (1 to 45 d). The BW, temperature, and FHP data were used to fit the simultaneous model. The procedure used in this study assumed two main stages: (i) how the CT ( °C) is affected by BW size and (ii) how the FHP changes according to T. To solve the first stage (i), the one-phase exponential decay was used to relate CT as a function of BW (1 - CT = c + (d - c) × e − R×BW). To solve the second stage (ii), a line-line regression was used to describe the amount of energy used (kcal/(kg0.75 × °C)) above FHP assuming a single CT (2 - FHPkcal/bird = BWb × [L + U × (CT - T) × (T < CT) + V × (T - CT) × (T ≥ CT)]). The CT term in equation 2 was replaced by equation 1, allowing for the building of a simultaneous model. A previous analysis showed that FHP was proportional to BW raised to the power of 0.75; thus this allometric scaling was used to adjust the full model. The fitted model was as follows: FHPkcal/bird = BW0.75 × [84.98 + 2.65 × (CT - T) × (T < CT) + 4.41 × (T - CT) × (T ≥ CT)], where CT = 22.46 + (35.83 - 22.46) × e − 0.4906×BW, BW is body weight (kg) and T is temperature ( °C). In the current study, the simultaneous regression analysis indicated that the CT decreases as BW increases, while the energy corrections outside CT are 2.70 and 4.07 kcal/kg0.75( °C × d) for temperatures below and above CT, respectively.
Keywords: Critical temperature; Energy for maintenance; Fasting heat production; Indirect calorimetry